1984
DOI: 10.1002/ajh.2830160308
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets in patients with aplastic anemia

Abstract: Lymphocyte subsets were enumerated in a group of 31 patients with aplastic anemia. Abnormal numbers of immunoregulatory T-cells were found in some patients: 26% of them showed a reversed helper/suppressor ratio. Seven of 18 patients showed significantly decreased proliferation in response to PWM; this hyporesponsiveness was present in 75% of patients with a reversed helper/suppressor ratio and in 10% of those with a normal helper/suppressor ratio (R = 0.66, P = 0.008). Eight of 18 patients showed suppressor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Aplastic anemia (AA) has been shown to be more frequent in Mexico than in Caucasian populations [67]. Interestingly, 50% of Mexican patients with AA in anemia have abnormalcies in the expression of CD55 and CD59, which suggests that they are hypoplastic variants of paroxysmal nocturnal hemoglobinuria [68].…”
Section: Aplastic Anemiamentioning
confidence: 99%
“…Aplastic anemia (AA) has been shown to be more frequent in Mexico than in Caucasian populations [67]. Interestingly, 50% of Mexican patients with AA in anemia have abnormalcies in the expression of CD55 and CD59, which suggests that they are hypoplastic variants of paroxysmal nocturnal hemoglobinuria [68].…”
Section: Aplastic Anemiamentioning
confidence: 99%
“…The use of antilymphocyte globulin in the treat ment of aplastic anemia goes back to early studies by Mathe et al [21]: its mechanism of action is not fully understood, but seems to be related to the abrogation of the number or function of some T-cell subsets, ap parently involved in the pathogenesis of aplastic anemia [6,13,22,23]. We have shown that domestic ATG abrogates the number of CD25( + ) cells (interleukin-2 receptor-bearing T cells) [20], that have pre viously been shown to play a role in the pathogenesis of some cases of SAA suggesting that this T-cell sub set may be involved in the origin of the immune sup pression of hematopoiesis in some cases of aplastic anemia [22], Similar results have been recently pub lished by Platanias et al [25] '...it is the same hypothe sis which ignited the first clinical studies with ATG, the only non-chimerizing treatment for SAA which, even if based on fallible assumptions and still obscure mechanisms, is capable of competing with BMT' [26].…”
Section: Discussionmentioning
confidence: 99%
“…The response and sur vival of patients with SAA treated with BMT + ATG, BMT alone or ATG alone does not seem to be very different [4], The role of androgens alone in the treat ment of SAA has been ruled out and is significantly lower than that of ATG [5]. SAA affects 5-30 new pa tients per million per year in Europe and a higher in cidence has been reported in Japan, China and Mex ico [6][7][8][9][10], BMT programs are expensive and, up to now, there is no one working regularly in our country where few BMTs have been performed [11], Even though the costs of the ATG infusion are lower than that of BMT, ATG is expensive in our country: only 10-15% of patients with SAA in Mexico can afford the costs of the ATG treatment. In an effort to make affordable the treatment for most patients with SAA in Mexico, the Agrupación Mexicana para el Estudio de la Hematología AC (Mexican Society of Hematol ogy), through its Grupo Cooperativo de Eritropatías y Hemopoyesis (Mexican Cooperative Group for the Study of Erythropathies and Hemopoiesis) started a program to produce a batch of equine ATG to be em ployed in patients with SAA.…”
mentioning
confidence: 99%
“…That an immune mechanism was the cause of most adult AA cases became evident four decades ago, when it was shown that in vitro T cells from AA patients suppressed hematopoiesis (Ruiz-Argüelles et al 1984); these inhibitory T cells were later identified as belonging to the CD8 ? subset (Zoumbos et al 1985).…”
Section: Introductionmentioning
confidence: 99%